2023
DOI: 10.3389/fcvm.2023.1140160
|View full text |Cite
|
Sign up to set email alerts
|

Estimated pulse wave velocity is associated with all-cause and cardio-cerebrovascular disease mortality in stroke population: Results from NHANES (2003–2014)

Abstract: BackgroundArterial stiffness is a significant determinant and evaluation of cardio-cerebrovascular disease and all-cause mortality risk in the stroke population. Estimated pulse wave velocity (ePWV) is a well-established indirect measure of arterial stiffness. We examined the association of ePWV with all-cause and cardio-cerebrovascular disease (CCD) mortality in the stroke population in a large sample of US adults.MethodsThe study design was a prospective cohort study with data from the National Health and Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In the Systolic Blood Pressure Intervention Trial, which included 9361 participants with high risk profiles, an elevated ePWV was associated with cardiovascular risk, independently of Framingham Risk scores [ 12 ]. Further studies have underscored the prognostic value of ePWV in stroke patients [ 13 ] and those with diabetes mellitus [ 21 ]. Yet, the significance of ePWV for patients undergoing a PCI has not been firmly established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Systolic Blood Pressure Intervention Trial, which included 9361 participants with high risk profiles, an elevated ePWV was associated with cardiovascular risk, independently of Framingham Risk scores [ 12 ]. Further studies have underscored the prognostic value of ePWV in stroke patients [ 13 ] and those with diabetes mellitus [ 21 ]. Yet, the significance of ePWV for patients undergoing a PCI has not been firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, PWV is determined by dividing the distance between two specific points by the time difference of pulse wave arrival using specialized equipment. However, it can also be estimated based on age and blood pressure (BP), the primary factors known to influence arterial elasticity [ 11 , 12 , 13 , 14 ]. In this study, we utilized this “estimated PWV (ePWV)” as a prognostic tool for patients who had undergone a PCI.…”
Section: Introductionmentioning
confidence: 99%
“…And SII is an emerging marker that can re ect the immune and in ammatory response of human body. It was rst de ned in 2014 as a novel in ammatory biomarker combining platelet count (PC), neutrophil count (NC), and lymphocyte count (LC) with the formula PC*NC / LC [14,15] . Numerous studies have demonstrated the promising value of SII in assessing the risk and prognosis of cardiovascular, metabolic, and immune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This result was confirmed by Vlachopoulos et al in very high-risk hypertensive patients (the SPRINT study), showing that ePWV predicted the primary composite CV outcome and all-cause death independent of the FRS [ 14 ]. Later on, observations that ePWV predicted all-cause and CV mortality independently of traditional CV risk factors were reported in the general population, apparently healthy individuals and high-risk patients [ 8 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, in most of these studies, several groups of subjects were excluded, so the results could not be extrapolated to the general population.…”
Section: Introductionmentioning
confidence: 99%